Study of Hemoptysis in a Tertiary Care Center of Province 1: Causes and Recurrences - Ghimire, Ram Hari; Ghimire, Ashima; Shreewastav, Rupesh Kumar; Yadav, Sushil; Bidesh Bista, Bidesh (Birat Journal of Health Sciences, 2020)
Introduction: Hemoptysis is a common but distressing and alarming symptom in a patient. Data related to detail clinical profile and follow up study of hemoptysis are lacking. Objective: This study was carried out to see the clinical profile of patients with hemoptysis and to study the recurrences in tertiary care centre of province 1 within the study period. Methodology: This was a prospective observational study conducted at the department of Pulmonary, Critical Care and Sleep Medicine of Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. The study was carried out between 30th January 2017 to 1st February 2020. For follow up of recurrences of hemoptysis, the patients were asked for regular chest clinic follow up and regular telephone calls made to the patients, in case, patients could not attend the chest clinic for any reason. Results: A total of 150 patients were enrolled over the last 3 years. Among them 75% were male. The maximum number of patients (27%) were between 31-40 years of age group. Old sequelae of pulmonary tuberculosis (PTB) (32%) and bronchiectasis (28%) were the commonest cause of hemoptysis. Lung cancer (10%) and active PTB (10%) were other causes of hemoptysis. CT scan of the chest provided the highest (84%) diagnostic yield. Most of the cases were having mild hemoptysis (50%). 17% of the patients in our study had recurrences of hemoptysis. Conclusion: Old PTB sequelae with bronchiectasis (fibrobronchiectasis) were the commonest cause of hemoptysis. Conservative management worked most effectively in controlling hemoptysis, if used properly.